Pediatric idiopathic midgut volvulus and shock in the infant - Maciel,Juliana (2020)
Abstract Introduction: Intestinal volvulus is a surgical emergency in which a segment of the intestine twists over its mesenteric attachment, causing bowel obstruction. It usually presents with bilious vomiting and can progress to bowel necrosis and shock. Case Report: A 40-days-old male infant presented with acute onset irritability, bilious vomiting, abdominal distention, and hematochezia. He rapidly evolved to shock with metabolic acidosis and coagulopathy, requiring fluid resuscitation, vasoactive agents, and invasive mechanical ventilation. The patient was submitted to urgent laparotomy, confirming midgut volvulus without malrotation. Partial reperfusion of the affected midgut was achieved, with no resection initially performed, but 48 hours later he was re-evaluated and partial enterectomy for midgut necrosis was performed. Despite the condition´s severity, the patient had a good evolution with full recovery. Discussion: Bilious vomiting in the infant is highly suggestive of intestinal obstruction. The authors emphasize the presence of midgut volvulus without malrotation, complicated with bowel necrosis and shock.